The prevalence of injuries in Jiu-Jitsu according to the report of the athletes participating in 2006 world championships - Machado, Adriano Pinheiro (2012)
Objective: To analyze the prevalence, anatomical location, situation of origin and occurrence, the removal and severity of injuries in Jiu-Jitsu athletes. Methods: A total of 308 athletes participated in this study. The assessment tool consisted of a closed questionnaire that was answered by the athletes. Results: The anatomical regions most affected were the knee (28.40%), shoulder (15.60%) and elbow (10.40%), and 42.80% of the injuries occurred when the athlete has received a stroke, and 15.60% when applying a stroke. Most of the injuries led the athletes to the removal of practice the sport (72%) and most injuries were severe (34%), occurring mostly during training (67.40%). Conclusions: This study contributed to the characterization of injuries in Jiu-Jitsu, as well as their causes, and raised awareness of the risks in this technique, making it possible to reduce the incidence and severity of injuries. We suggest further studies and the development of preventive measures for avoiding injury in the sport.